Development of Molecular Markers Linked to Powdery Mildew Resistance Gene Pm4b by Combining SNP Discovery from Transcriptome Sequencing Data with Bulked Segregant Analysis (BSR-Seq) in Wheat - Wu, Peipei; Xie, Jingzhong; Hu, Jinghuang; Qiu, Dan; Liu, Zhiyong; Li, Jingting; Li, Miaomiao; Zhang, Hongjun; Yang, Li; Liu, Hongwei; Zhou, Yang; Zhang, Zhongjun; et al. (Frontiers in Plant Science, 2018)
Powdery mildew resistance gene Pm4b, originating from Triticum persicum, is effective against the prevalent Blumeria graminis f. sp. tritici (Bgt) isolates from certain regions of wheat production in China. The lack of tightly linked molecular markers with the target gene prevents the precise identification of Pm4b during the application of molecular marker-assisted selection (MAS). The strategy that combines the RNA-seq technique and the bulked segregant analysis (BSR-seq) was applied in an F2:3 mapping population (237 families) derived from a pair of isogenic lines VPM1/7*Bainong 3217 F4 (carrying Pm4b) and Bainong 3217 to develop more closely linked molecular markers. RNA-seq analysis of the two phenotypically contrasting RNA bulks prepared from the representative F2:3 families generated 20,745,939 and 25,867,480 high-quality read pairs, and 82.8% and 80.2% of them were uniquely mapped to the wheat whole genome draft assembly for the resistant and susceptible RNA bulks, respectively. Variant calling identified 283,866 raw single nucleotide polymorphisms (SNPs) and InDels between the two bulks. The SNPs that were closely associated with the powdery mildew resistance were concentrated on chromosome 2AL. Among the 84 variants that were potentially associated with the disease resistance trait, forty-six variants were enriched in an about 25 Mb region at the distal end of chromosome arm 2AL. Four Pm4b-linked SNP markers were developed from these variants. Based on the sequences of Chinese Spring where these polymorphic SNPs were located, 98 SSR primer pairs were designed to develop distal markers flanking the Pm4b gene. Three markers, Xics13, Xics43 and Xics76, were incorporated in the new genetic linkage map, which located Pm4b in a 3.0 cM genetic interval spanning a 6.7 Mb physical genomic region. This region had a collinear relationship with Brachypodium distachyum chromosome 5, rice chromosome 4, and sorghum chromosome 6. Seven genes associated with disease resistance were predicted in this collinear genomic region, which included protein kinases of PKc_like super family, C2 domain protein, peroxidase activity protein, Mlo family protein, and catalytic domain of the serine/threonine kinases (PKc_like super family). The markers developed in the present study facilitate identification of Pm4b during its MAS practice. Keywords: Powdery mildew, Pm4b, BSR-seq,